Ceratoplastia com recobrimento de terceira pálpebra em felino doméstico para o tratamento de descemetocele com perfuração de córnea - Abreu, Wandercleyson Uchôa; Philippsen, Caroline; Lima, Dennis José da Silva (Acta Scientiae Veterinariae, 2017)
Background: Descemetocele is a lesion on the descemet’s membrane most often caused by very deep ulcerations in the cornea, where the epithelium, basement membrane and stroma layers are exposed, leading to a distortion of the corneal structure. Because it is an injury whose evolution can lead to loss of vision, Descemetocele is considered a surgical emergency because, within the various techniques adopted, there is always an attempt to preserve the ocular bulb. Thus, the adoption of various reconstructive keratoplasty procedures have been described in descemet’s membrane repair and ocular perforations of varying degrees of extension. In this surgical technique, tissue fragments (autogenous, autologous or xenologous) are usually used, the surgical method being defined according to the degree of injury (partial or total) and the amount of tissue required to be replaced. The aim of this study was to report a case of Keratoplasty with a third eyelid covering for descemetocele correction with corneal perforation in a domestic cat. Case: A 2-year-old feline female was treated at the Veterinary Hospital of the University of Amazonia (UNAMA), presenting a traumatic ocular lesion with evolution of more than 25 days, refractory to treatment as eye drops. The ophthalmologic examination revealed presence of extravasated polymerized necrotic tissue in the cornea of the left eye, with Descemetocele as diagnosis. The treatment indicated was Reconstructive Keratoplasty without graft with third eyelid coating. As an anesthetic protocol, MPA was used with acepromazine, ketamine hydrochloride as the inducing agent and isoflurane in mask vaporization for the maintenance of the anesthetic plane. After preparation of the patient, the surgical procedure consisted of excision with a scalpel blade of the necrotic tissue, exposure of the endothelial layer and suture of the cornea with Vincryl®, in a simple discontinuous pattern. The third eyelid flap was then recovered by traction and fixation of the lesion in the direction of its movement, using the discontinuous (U-shaped) Wolf suture with Vincryl®. For the postoperative period cephalexin 30.0 mg kg-1 BID was prescribed for 10 days and ketoprofen 2.0 mg kg-1 SID was prescribed for 4 days and the use of Elizabethan collar was recommended. After 20 days, the animal returned and the corneal integrity returned. Discussion: Many inflammatory and infectious conditions can cause Descemetocele. In the case presented here, among these conditions, trauma with secondary bacterial infection, leading to chronic corneal ulceration was determinant for the appearance of this disease. The main therapeutic goal in these cases is to provide support from the Descemetocele area to prevent imminent leakage of the aqueous humor. Tissue adhesives, therapeutic contact lenses (TBCLs), membrane transplantation, among other techniques, have been reported for the treatment of this disease. In the case of the feline in question, the surgical therapy of Keratoplasty was adopted, a technique recommended for the correction of corneal damage. The coating with the third eyelid set in the Keratoplasty for Descemetocele correction was already described in cats and also followed in the present study. Severe complications after surgical treatment of descemetocele with corneal perforation may occur, however, during the treatment instituted in the feline patient, the method was completely successful.